Zinc oxide hollow fiber membrane containing inorganic additive and preparation method thereof

By introducing zinc oxide and surfactant into the hollow fiber membrane and designing multi-layer structures and finger-like pores, the problems of insufficient pollution resistance and mechanical strength of the membrane are solved, and higher pollution resistance and mechanical properties are achieved.

CN119819133APending Publication Date: 2025-04-15湖北魔方新能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510091838.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing hollow fiber membranes have insufficient pollution resistance and mechanical strength when dealing with complex fluids, resulting in reduced membrane flux and structural damage.

Method used

Using zinc oxide hollow fiber membranes containing inorganic additives, the inner membrane layer, hollow layer and outer membrane layer are arranged, and finger-like pore structures are designed inside the hollow layer, combined with the use of polysulfone polymers and surfactants, the mechanical properties and soil resistance of the membrane are improved.

Benefits of technology

It significantly improves the film's stain resistance and mechanical properties, extends the film's service life, reduces the difficulty and frequency of cleaning, and enhances the stability of the film under high pressure and high flow velocity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819133A_ABST
    Figure CN119819133A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc oxide hollow fiber membrane containing an inorganic additive and a preparation method of the zinc oxide hollow fiber membrane, and belongs to the technical field of membranes. The zinc oxide hollow fiber membrane comprises an inner membrane layer, a hollow layer and an outer membrane layer which are sequentially arranged, and finger-shaped holes are formed in the hollow layer. The invention also provides a preparation method of the zinc oxide hollow fiber membrane, which comprises the following steps: dissolving the Tween-60, the PEG-400, the additive and the non-solvent additive in a solvent in a reaction kettle, then adding the polysulfone polymer, and stirring and heating to obtain a mixed solution; performing vacuum defoaming on the mixed solution to obtain a membrane casting solution; and introducing the membrane casting solution into an annular spinning nozzle for extrusion, introducing the core solution into an inner cavity of the annular spinning nozzle at the same time, spinning, carrying out air bath, entering a gel tank, carrying out phase inversion curing to form a hollow fiber ultrafiltration membrane, and carrying out drafting, rolling, cleaning and drying to obtain the zinc oxide hollow fiber membrane. The hollow fiber membrane disclosed by the invention is good in pollution resistance and strong in mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thin films, and in particular relates to a zinc oxide hollow fiber membrane containing an inorganic additive and a preparation method thereof. Background Art

[0002] As an efficient, energy-saving and environmentally friendly separation and purification method, membrane separation technology plays a key role in many fields of modern industrial production and daily life. Hollow fiber membranes stand out among many membrane materials with their unique structure and excellent performance, such as large specific surface area, high flux and good separation selectivity, and are widely used in chemical, food, medicine, environmental protection, seawater desalination and other industries.

[0003] However, hollow fiber membranes currently face many severe challenges in practical applications, among which the membrane's pollution resistance and mechanical strength problems are particularly prominent, which seriously restricts their further promotion and application.

[0004] In terms of pollution resistance, with the rapid development of industry and the intensification of water resource pollution, the composition of the fluid treated by the hollow fiber membrane has become increasingly complex. Whether it is the wastewater generated in the industrial production process, which may contain high concentrations of organic pollutants, heavy metal ions, suspended particles, etc., or the fermentation broth in the biopharmaceutical field, which is rich in biological macromolecules such as proteins, polysaccharides, and microbial cells, these complex components are very easy to adsorb, deposit and clog on the membrane surface. Once the pollutants accumulate on the membrane surface, a dense pollution layer will quickly form, hindering the permeation of solutes and solvents, causing the membrane flux to decrease exponentially. For example, when treating printing and dyeing wastewater, pollutants such as dye molecules and auxiliaries in the wastewater will be adsorbed on the membrane surface in a short time, reducing the membrane flux by more than 50% within a few hours. Moreover, this pollution phenomenon not only reduces the separation efficiency of the membrane, but also greatly increases the difficulty and frequency of membrane cleaning. Traditional physical cleaning methods, such as backwashing and ultrasonic cleaning, are often difficult to completely remove stubborn pollutants; and although chemical cleaning is relatively effective, the frequent use of chemical cleaning agents will cause irreversible damage to the membrane material, shorten the service life of the membrane, and increase the cost of use.

[0005] In terms of mechanical strength, hollow fiber membranes usually have a large aspect ratio due to their own structural characteristics, which makes them more fragile when subjected to external forces. In the actual preparation and installation process of membrane components, it is inevitable that certain tensile, bending and torsional forces will be applied to the membrane. If the mechanical strength of the membrane is insufficient, it is easy to cause problems such as breakage and fracture. In addition, during the operation of the membrane, especially under high pressure and high flow rate conditions, such as in the reverse osmosis process of seawater desalination, the membrane needs to withstand pressures of up to tens of megapascals, as well as the shear force generated by the high-speed flow of the fluid. When the mechanical strength of the membrane cannot meet the requirements of these working conditions, the structure of the membrane will be destroyed, resulting in loss of separation performance. According to statistics, in some membrane systems operating at high pressure, membrane damage accidents caused by insufficient mechanical strength account for more than 30% of the total failures, seriously affecting the stable operation of the membrane system.

[0006] In recent years, membrane separation, as a new, efficient and energy-saving technology, has been widely used in the fields of food industry, pharmaceutical and bioengineering, petrochemical industry, seawater desalination, pure water preparation, industrial wastewater treatment, domestic sewage treatment, etc. In industrial applications, China has made significant progress in the research and development of water treatment membrane technology and has developed a variety of new water treatment membranes, such as flat membranes, composite reverse osmosis membranes and hollow fiber membranes. This kind of membrane has great strength, can operate under a large pressure gradient, will not be compressed and creep, and thus has good mechanical properties. Some membranes on the market have disadvantages such as poor resistance to pollution and insufficient mechanical strength. Summary of the invention

[0007] The invention provides a zinc oxide hollow fiber membrane containing an inorganic additive and a preparation method thereof, so as to solve the technical problems of poor antifouling property and mechanical property of the fiber membrane in the prior art.

[0008] To achieve the above technical purpose, the present invention provides a zinc oxide hollow fiber membrane containing an inorganic additive, comprising an inner membrane layer, a hollow layer and an outer membrane layer arranged in sequence, wherein the hollow layer has finger-like holes inside.

[0009] Preferably, the composition comprises, by weight, 10-20 parts of polysulfone polymer, 50-70 parts of solvent, 1-5 parts of Tween-60, 1-5 parts of PEG-400, 1-10 parts of additives and 2-5 parts of non-solvent additives.

[0010] Preferably, the polysulfone polymer is one or both of polysulfone and polyethersulfone.

[0011] Preferably, the solvent is one or two of dimethylformamide, dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0012] Preferably, the additive is a mixture of zinc oxide and polyethylene glycol or polyvinyl pyrrolidone.

[0013] Preferably, the non-solvent additive is one or a mixture of two or more of water, ethanol and glycerol.

[0014] A method for preparing the zinc oxide hollow fiber membrane as described above comprises the following steps:

[0015] S1, dissolving Tween-60, PEG-400, additives and non-solvent additives in a solvent in a reaction kettle, adding a polysulfone polymer, stirring and heating to obtain a mixed solution;

[0016] S2, vacuum degassing the mixed solution to obtain a casting solution;

[0017] S3, passing the casting liquid into an annular spinneret for extrusion, and at the same time passing the core liquid into the inner cavity of the annular spinneret for spinning, and entering the gel tank after an air bath for phase inversion and solidification to form a hollow fiber ultrafiltration membrane, and obtaining the zinc oxide hollow fiber membrane after drawing, winding, washing and drying.

[0018] Preferably, the vacuum degassing temperature in S2 is 60-90° C., and the degassing time is 10-15 hours.

[0019] Preferably, the core liquid in S3 is a mixture of solvent 2 and pure water, and the mass ratio of solvent 2 to pure water is 21 to 1:9.

[0020] Preferably, the spinning pressure in S3 is 0.2-0.3 MPa, the ambient temperature is 27-30° C., and the ambient humidity is 50-65% RH.

[0021] Zinc oxide has certain antibacterial properties, which can inhibit the growth and reproduction of bacteria and other microorganisms on the membrane surface, and reduce the pollution caused by microbial attachment. At the same time, zinc oxide may have an adsorption or catalytic decomposition effect on some organic pollutants, which helps to keep the membrane surface clean. When used in combination with surfactants Tween-60 and PEG-400, it can reduce the surface tension of the membrane surface, making it easier for water to spread on the membrane surface, reducing the adsorption of pollutants on the membrane surface, and making the membrane surface less likely to be attached by pollutants such as oil.

[0022] Polysulfone polymers themselves have good mechanical properties, such as high strength and high toughness. During the formation of the membrane, polysulfone polymers form a continuous network structure, which provides basic mechanical support for the membrane. The mixture of zinc oxide and polyethylene glycol or polyvinyl pyrrolidone as an additive can interact with polysulfone polymers. On the one hand, zinc oxide can fill the gaps in the polymer network and play a reinforcing role; on the other hand, polyethylene glycol or polyvinyl pyrrolidone can improve the compatibility and bonding between polymers, further improving the mechanical strength of the membrane.

[0023] Influence of membrane structure: The multilayer structure design of inner membrane layer, hollow layer and outer membrane layer and the finger-like hole structure inside the hollow layer help to improve the overall mechanical properties of the membrane. This structure can increase the structural stability of the membrane while ensuring the air permeability and water permeability of the membrane, making it more able to withstand external forces.

[0024] Compared with the prior art, the beneficial effects of the present invention include:

[0025] The present invention forms a sponge-like pore structure by adding non-solvent additives and adjusting the preparation process, so that the membrane itself has a good low molecular weight interception effect and improves mechanical properties; by adding surfactants Tween-60 and PEG-400, the diffusion resistance between the solvent and the non-solvent is increased, the phase separation time is delayed, and it is beneficial to the uniform distribution of pores; through dry-wet spinning, the preparation process is simple to operate, the reaction conditions are mild, and it is safe and efficient. The prepared central control film has good anti-fouling and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The microstructure of a zinc oxide hollow fiber membrane containing an inorganic additive provided in Example 1 of the present invention;

[0027] Figure 2 This is another microstructure of the zinc oxide hollow fiber membrane containing inorganic additives provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0029] Example 1

[0030] The present embodiment provides a zinc oxide hollow fiber membrane containing an inorganic additive, comprising an inner membrane layer, a hollow layer and an outer membrane layer arranged in sequence, wherein the hollow layer has finger-like holes inside. The zinc oxide hollow fiber membrane comprises, by mass, 10 parts of polysulfone, 50 parts of dimethylformamide, 1 part of Tween-60, 1 part of PEG-400, 0.5 parts of zinc oxide, 0.5 parts of polyethylene glycol, 1 part of water and 1 part of ethanol.

[0031] A method for preparing the zinc oxide hollow fiber membrane as described above comprises the following steps:

[0032] S1. Dissolve Tween-60, PEG-400, additives and non-solvent additives in the solvent in the reaction kettle, add the polysulfone polymer, stir and heat to obtain a mixed solution, the stirring and heating temperature is 60° C., and the stirring time is 20 h;

[0033] S2, vacuum degassing the mixed solution to obtain a casting solution, the vacuum degassing temperature is 60° C., and the degassing time is 15 h;

[0034] S3. The casting liquid is passed into an annular spinneret for extrusion, and the core liquid is passed into the inner cavity of the annular spinneret for spinning. The core liquid is a mixture of dimethylformamide and pure water, and the mass ratio of dimethylformamide to pure water is 7:3. The spinning pressure is 0.2Mpa, the ambient temperature is 27°C, and the ambient humidity is 50%RH. After an air bath and a coagulation bath, the mixture enters a gel tank for phase inversion and solidification to form a hollow fiber ultrafiltration membrane. After stretching, winding, cleaning and drying, the zinc oxide hollow fiber membrane is obtained.

[0035] The microstructure of the zinc oxide hollow fiber membrane prepared in this example is shown in FIG. Figure 1 and Figure 2 shown.

[0036] Example 2

[0037] The present embodiment provides a zinc oxide hollow fiber membrane containing an inorganic additive, comprising an inner membrane layer, a hollow layer and an outer membrane layer arranged in sequence, wherein the hollow layer has finger-like holes inside. The zinc oxide hollow fiber membrane comprises, by mass, 20 parts of polyethersulfone, 70 parts of dimethylacetamide, 5 parts of Tween-60, 5 parts of PEG-400, 2 parts of zinc oxide, 2 parts of polyvinyl pyrrolidone, 2 parts of ethanol and 1 part of glycerol.

[0038] A method for preparing the zinc oxide hollow fiber membrane as described above comprises the following steps:

[0039] S1. Dissolve Tween-60, PEG-400, additives and non-solvent additives in the solvent in the reaction kettle, then add the polysulfone polymer, stir and heat to obtain a mixed solution, the stirring and heating temperature is 90° C., and the stirring time is 20 h;

[0040] S2, vacuum degassing the mixed solution to obtain a casting solution, the vacuum degassing temperature is 90° C., and the degassing time is 10 h;

[0041] S3. The casting liquid is passed into an annular spinneret for extrusion, and the core liquid is passed into the inner cavity of the annular spinneret for spinning. The core liquid is a mixture of dimethylformamide and pure water, and the mass ratio of dimethylformamide to pure water is 1:9. The spinning pressure is 0.3Mpa, the ambient temperature is 30°C, and the ambient humidity is 65%RH. After an air bath and a coagulation bath, the mixture enters a gel tank for phase inversion and solidification to form a hollow fiber ultrafiltration membrane. After drawing, winding, cleaning and drying, the zinc oxide hollow fiber membrane is obtained.

[0042] Example 3

[0043] The present embodiment provides a zinc oxide hollow fiber membrane containing an inorganic additive, comprising an inner membrane layer, a hollow layer and an outer membrane layer arranged in sequence, wherein the hollow layer has finger-like holes inside. The zinc oxide hollow fiber membrane comprises, by mass, 15 parts of polysulfone, 30 parts of N-methylpyrrolidone, 30 parts of dimethyl sulfoxide, 4 parts of Tween-60, 3 parts of PEG-400, 5 parts of zinc oxide, 5 parts of polyvinylpyrrolidone, 2 parts of water and 3 parts of glycerol.

[0044] A method for preparing the zinc oxide hollow fiber membrane as described above comprises the following steps:

[0045] S1. Dissolve Tween-60, PEG-400, additives and non-solvent additives in the solvent in the reaction kettle, add the polysulfone polymer, stir and heat to obtain a mixed solution, the stirring and heating temperature is 80° C., and the stirring time is 15 h;

[0046] S2, vacuum degassing the mixed solution to obtain a casting solution, the vacuum degassing temperature is 80° C., and the degassing time is 13 h;

[0047] S3. The casting liquid is passed into an annular spinneret for extrusion, and the core liquid is passed into the inner cavity of the annular spinneret for spinning. The core liquid is a mixture of dimethylformamide and pure water, and the mass ratio of dimethylformamide to pure water is 10:9. The spinning pressure is 0.25 MPa, the ambient temperature is 29°C, and the ambient humidity is 60% RH. After an air bath and a coagulation bath, the mixture enters a gel tank for phase inversion and solidification to form a hollow fiber ultrafiltration membrane. After stretching, winding, cleaning and drying, the zinc oxide hollow fiber membrane is obtained.

[0048] Comparative Example 1

[0049] This comparative example is similar to Example 1, except that in this comparative example, an equal amount of zinc oxide is replaced by polyvinyl pyrrolidone.

[0050] The fiber membranes in Examples 1-3 and Comparative Example 1 were tested for mechanical properties. The test results are shown in Table 1.

[0051] Table 1 Test results of mechanical properties of fiber membranes in each group

[0052] Group StrengthMpa Maximum pulling force N Example 1 10.05 5.24 Example 2 12.21 6.58 Example 3 15.33 7.40 Comparative Example 1 8.31 4.23

[0053] The pure water flux, attenuation rate and retention rate of the hollow fiber membranes in Examples 1-3 and Comparative Example 1 were tested. The test results are shown in Table 2.

[0054] Table 2 Pure water flux, attenuation rate and retention rate test results

[0055]

[0056] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A zinc oxide hollow fiber membrane containing an inorganic additive, characterized in that: The invention comprises an inner film layer, a hollow layer and an outer film layer which are arranged in sequence, and the inner part of the hollow layer is provided with finger-shaped holes.

2. The zinc oxide hollow fiber membrane according to claim 1, characterized in that The composition comprises, by weight, 10-20 parts of a polysulfone polymer, 50-70 parts of a solvent, 1-5 parts of Tween-60, 1-5 parts of PEG-400, 1-10 parts of an additive and 2-5 parts of a non-solvent additive.

3. The zinc oxide hollow fiber membrane according to claim 2, characterized in that: The polysulfone polymer is one or both of polysulfone and polyethersulfone.

4. The zinc oxide hollow fiber membrane according to claim 2, characterized in that: The solvent is one or two of dimethylformamide, dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

5. The zinc oxide hollow fiber membrane according to claim 2, characterized in that: The additive is a mixture of zinc oxide and polyethylene glycol or polyvinyl pyrrolidone.

6. The zinc oxide hollow fiber membrane according to claim 2, characterized in that: The non-solvent additive is one or a mixture of two or more of water, ethanol and glycerol.

7. A method for preparing a zinc oxide hollow fiber membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, dissolving Tween-60, PEG-400, additives and non-solvent additives in a solvent in a reaction kettle, adding a polysulfone polymer, stirring and heating to obtain a mixed solution; S2, vacuum degassing the mixed solution to obtain a casting solution; S3, passing the casting liquid into an annular spinneret for extrusion, and at the same time passing the core liquid into the inner cavity of the annular spinneret for spinning, and entering the gel tank after an air bath for phase inversion and solidification to form a hollow fiber ultrafiltration membrane, and obtaining the zinc oxide hollow fiber membrane after drawing, winding, washing and drying.

8. The preparation method according to claim 7, characterized in that: The vacuum degassing temperature in S2 is 60-90° C., and the degassing time is 10-15 hours.

9. The preparation method according to claim 7, characterized in that: The core liquid in S3 is a mixture of solvent 2 and pure water, and the mass ratio of solvent 2 to pure water is 21 to 1:

9.

10. The preparation method according to claim 7, characterized in that: The spinning pressure in S3 is 0.2-0.3 MPa, the ambient temperature is 27-30° C., and the ambient humidity is 50-65% RH.